National Minorities and the state power of Ukraine in the early 1990s: the beginning of a constructive dialogue and lost prospects. - Kotsur L. М. (Вісник Черкаського університету. Серія: Історичні науки, 2016)
One of them ostimportant state’sassignments wastheassistance of pursuing personnel policy which was directed on representation guarantee of Ukrainian citizens of differenteth nicoriginin stateand facilities administration bodies. Hence, representatives of the most affluent national minorities’ organizations (Crimean Tatars, Germans, Jewish, Greeks etc.) launched active political struggle for their representation in state authority bodies of all levels. Most sensible this struggle was between National Communities Board of Ukraine which took authority’s side and Nationalities Board of National Movement of Ukraine which was in opposition. Due to the fact that National Communities Board had an active co-operation with state and political figures which came to power, its representatives had more chances to get in higher bodies of authority. Representatives of Board of National Movement didn’t have such opportunity insomuch as National Movement of Ukraine Party hadn’t totally won the elections. At the same time, majority of national and cultural communities which entered into relations with bodies of state authority longed to solve immediate matters concerning socio-economical, juridical, material, cultural and mental security of their rights. National and cultural communities and separate representatives of national minorities made a great contribution to the activity of Nationalities Committeewith the Cabinet of Ministers of Ukraine regarding developing of theoretical and accomplishing practical measures of satisfying needs of national minorities of Ukraine and in legislation sphere. Alsoit’ sclarified pros and cons of state ethnic policy in the field of ensuring political rights of national minorities of Ukraine.